Một số khía cạnh trần thuật trong tiểu thuyết - Trương, Thuận (Trường Đại học Đà Lạt, 2012)
Novel is a major literary genre that is typical of narration, the "head machine" of modern literature. with their own prosodical distinctions in narrative, novels capture and reflect the realities of life in a dimentional and profound way. Studying the narrative issue in novels specifically and literature in general helps us better understand an basic aspect of genre prosody.